1997
DOI: 10.2136/sssaj1997.03615995006100030025x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Corn Production and Reducing Nitrate Losses with Water Table Control‐Subirrigation

Abstract: Water table control‐subiriggation (WTC) systems have increased crop production and improved water quality; however, the relationship between N management, water table depths, and corn production has not been well defined. We hypothesized that optimizing water table depth would increase corn (Zea mays L.) growth, improve N fertilizer efficiency, and reduce NO‐3 losses. A greenhouse incubation study with three water table depths (30, 60, and 80 cm) and four N rates (0, 0.7, 1.4, and 2.1 g N plant‐1) was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Raising the water table by subirrigation increases soil saturation and restricts O 2 diffusion in soil pores, thus creating reducing conditions that promote NO − 3 losses by denitrification. Drury et al (1997) reported that a SI system reduced NO − 3 concentration in tile drainage water by 25% compared with a free drainage (FD) system. Similarly, Jacinthe et al (1999) estimated a 40% reduction in soil NO − 3 due to denitrification in SI plots compared with FD plots.…”
mentioning
confidence: 99%
“…Raising the water table by subirrigation increases soil saturation and restricts O 2 diffusion in soil pores, thus creating reducing conditions that promote NO − 3 losses by denitrification. Drury et al (1997) reported that a SI system reduced NO − 3 concentration in tile drainage water by 25% compared with a free drainage (FD) system. Similarly, Jacinthe et al (1999) estimated a 40% reduction in soil NO − 3 due to denitrification in SI plots compared with FD plots.…”
mentioning
confidence: 99%
“…The effective incorporation of OC into soils is lower than 50% (McCracken et al, 2002). Nevertheless, irrigation with diluted OOMW and water bubbled with CO 2 , could improve the retention capacity of water, nitrates, and other soil nutrients (Drury et al, 1997;Neilsen et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…This occurrence may have facilitated nutrient movement in the bed and eventual loss from the root zone once nutrients reached the bottom layer, particularly NO^^-N and K ( Fig. 2a; Drury et al, 1997;Zeng and Brown, 2000). This could explain why TN¡ in the soil increased during 6 to 8 WAP, then dropped considerably at 10 WAP in the spring season concurrently with the fluctuation ofthe volumetric water content, while TNj in the bed steadily decreased with time in the winter season (Fig.…”
Section: Water Movementmentioning
confidence: 96%